Arab Contemporary : Architecture & Identity (Louisiana Museum of Modern Art, 2014)
Arab Contemporary is the second chapter in the Louisiana Museum of Modern Art$1 (Bs Architecture, Culture and Identity series, following 2012$1 (Bs New Nordic, which explores architecture in specific regions. Arab Contemporary attempts to distinguish particular features of architecture that are shared by Arab countries from the Arab Peninsula through Lebanon to Morocco. While these areas are primarily connected via a common language, they further share major elements of visual culture, such as the use of calligraphy in architecture. Ranging over varied architectural works as well as visual arts, this volume showcases architecture by Ateliers Jean Nouvel, X-Architects, Henning Larsen Architects and many others, alongside artwork by Egyptian visual artist Mounir Fatmi, the Saudi artist Ahmed Mater, art historian and graphic artist Bahia Shehab and the Tuareg author Ibrahim al-Koni.s
English
Keywords: NA1-60 Architecture- General